Penentuan Kurva Retensi Air Tanah Laboratorium dengan Sensor Resistensi dan Kapasitansi - Bowo, Cahyoadi; Hasan, Mohammad; Marhaenanto, Bambang (JOURNAL OF TROPICAL SOILS, 2009)
A soil water retention curve determination method is developed based on the use of gipsblock and capacitance sensors. The objective of the research was to provide a simple and quick method in characterization of soil water retention in the laboratory based on resistance and capacitance sensors. Undisturbed soil sample collected using stainless steel ring sampler 8cm in diameter and 6cm height. Digital gipsblock and capacitance sensors connected to personal computer detected periodically water tension and volumetric water content of the sample. To test the reliability of collected data, measurement using pressure plate apparatus was also conducted. Result of the experiment for soil samples textural classes loam to clay loam leaded well compromise with result from pressure plate. However, significant deviation of soil water content has been detected as theÂ  soil water suction exceeded 15,000hPa. Deviation of measured water content increased with the reducing water content up to 0.300cm3.cm-3. Implication of this result showed a further finer standardization assesing water tension above 10.000hPa is needed.